Actor-Network Theory of Cosmopolitan Education - SAITO, Hiro (Institutional Knowledge at Singapore Management University, 2010)
In the past, philosophers discussed cosmopolitanism as a normative ideal of allegiance to humanity as a whole. A debate among social theorists, however, has examined cosmopolitanism as an incipient empirical phenomenon: an orientation of openness to foreign others and cultures. This paper introduces actor-network theory to elaborate the social-theoretical conception of cosmopolitanism. In light of the actor-network theory of cosmopolitanism, the paper proposes cosmopolitan education that aims to foster in students three dispositions: to extend attachments to foreign people and objects; to understand transnational connections in which their lives are embedded; and to act on these attachments and understandings to effect transformations across national borders. Through this three-fold cosmopolitan education, students will grow to be citizens of the world who traverse national borders dialogically by virtue of their transnational attachments, understandings, and actions.